Autoimmune Polyglandular Syndrome Type 3c with Ectodermal Dysplasia, Immune Deficiency and Hemolytic-Uremic Syndrome - Büyükçelik, Mithat (Galenos Publishing, 2014)
Autoimmune polyglandular syndrome (APS) is a disorder which is associated with multiple endocrine gland insufficiency and also with non-endocrine manifestations. The pathophysiology of APS is poorly understood, but the hallmark evidence of APS is development of autoantibodies against multiple endocrine and non-endocrine organs. These autoantibodies are responsible for the dysfunction of the affected organs and sometimes may also cause non-endocrine organ dysfunction. The hemolytic-uremic syndrome (HUS) is a serious and life-threatening disease which develops due to many etiological factors including autoimmune disorders. Here, we present an unusual case of APS. Ectodermal dysplasia with immune deficiency and HUS occurred concomitantly in the same patient with APS type 3c. Once the autoantibody generation was initiated in the human body, development of multiple disorders due to organ dysfunction and also autoantibody-related diseases may have occurred.